“Manajemen Strategis Transformasi Digital dalam Pembelajaran Akidah Akhlak di Madrasah Aliyah.” - Sabila Qurrota A'yun; Nadia Putri Kamila; Fisman Bedi; Heru Juabdin Sada (At Turots: Jurnal Pendidikan Islam, 2026)
The development of an entrepreneurial mindset among students has become increasingly important in responding to the challenges of the digital era and global competition. Higher education institutions, particularly in the field of Islamic Education Management, are required to implement effective learning models that can foster creativity, innovation, and independence. One of the approaches considered effective is Project-Based Learning (PjBL), which emphasizes active student involvement through real-world projects. This study aims to analyze the effectiveness of Project-Based Learning in improving the entrepreneurial mindset of Islamic Education Management students through a systematic literature review approach. The data were collected from various scientific articles published between 2019 and 2025, sourced from reputable databases such as Google Scholar and indexed journals. The novelty of this study lies in its specific focus on the integration of Project-Based Learning within the context of Islamic Education Management, which has received limited attention in previous studies, as well as in its comprehensive synthesis of recent empirical findings to identify patterns, challenges, and pedagogical implications. The findings indicate that Project-Based Learning significantly contributes to the development of entrepreneurial mindset dimensions, including creativity, problem-solving skills, risk-taking ability, and self-confidence. Furthermore, PjBL provides experiential learning that bridges theoretical knowledge and practical application. However, several challenges were identified, such as limited institutional support and the need for lecturer competency in facilitating project-based instruction. This study concludes that Project-Based Learning is an effective pedagogical strategy in fostering entrepreneurial mindset among students, particularly in Islamic Education Management programs, although its implementation requires systematic support and proper instructional desig